Manpower Modeling and Sensitivity Analysis for Afghan Education Policy - Marlin, Benjamin; Sohn, Hansuk (International Journal of Industrial Engineering: Theory, Applications and Practice, 2013)
<span style="font-family: "Times New Roman","serif"; font-size: 10pt; mso-fareast-font-family: "Malgun Gothic"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-fareast-theme-font: minor-fareast; mso-no-proof: yes;">This paper provides a demand based balance of flow manpower model premised in mathematical programming to provide insight into the potential futures of the Afghan Education System. Over the previous three decades, torn from multiple wars and an intolerant governing regime, the education system in Afghanistan has been decimated. Over the past 10 years Afghanistan and the international community have dedicated a substantial amount of resources to educate the youth of Afghanistan. By forecasting student demand we are able to determine points of friction in the teacher production policy regarding grade level, gender, and province across a medium-term time horizon. We modify the model to provide sensitivity analysis to inform policies. Examples of such policies are accounting for the length of teacher training programs and encouragement of inter-provincial teacher moves. By later applying a stochastic optimization model potential outcomes regarding changes in teacher retention attributed to policy decisions, incentives to teach, or security concerns are highlighted. This model was developed in support of the validation of a large scale simulation regarding the same subject.